Effects of open-air sun drying and pre-treatment on drying characteristics of purslane (Portulaca oleracea L.) - Ismail, Osman; Figen, Aysel Kanturk; Piskin, Sabriye (SPRINGER, 2015)
Effects of open-air sun drying and pre-treatment on drying characteristic of purslanes (Portulaca oleracea L.) were investigated. Drying times were determined as 31, 24 and 9 h for natural, salted and blanched, respectively. The higher L value and lower -a/b ratio values were obtained in natural dried purslane. The Aghbashlo et al. model gave a better fit to drying data.
Keywords: LAYER; KINETICS; DEHYDRATION; LEAVES; FRUITS; Thermodynamics; Mechanics